2023
DOI: 10.1155/2023/2738351
|View full text |Cite
|
Sign up to set email alerts
|

Rutin and Hesperidin Revoke the Hepatotoxicity Induced by Paclitaxel in Male Wistar Rats via Their Antioxidant, Anti‐Inflammatory, and Antiapoptotic Activities

Abstract: Paclitaxel, one of the most effective chemotherapeutic drugs, is used to treat various cancers but it is exceedingly toxic when used long-term and can harm the liver. This study aimed to see if rutin, hesperidin, and their combination could protect male Wistar rats against paclitaxel (Taxol)-induced hepatotoxicity. Adult male Wistar rats were subdivided into 5 groups (each of six rats). The normal group was orally given the equivalent volume of vehicles for 6 weeks. The paclitaxel-administered control group re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 120 publications
0
4
0
Order By: Relevance
“…Hesperidin, detected in relatively high amounts in the T. pallidus extract, has a well-documented history of exhibiting potent antioxidant properties. Moreover, numerous studies have reported its efficacy in attenuating inflammatory responses [13]. These findings indicate that thyme may hold promise as an anti-inflammatory agent, particularly due to its high content of hesperidin.…”
Section: Phytochemical Studymentioning
confidence: 92%
“…Hesperidin, detected in relatively high amounts in the T. pallidus extract, has a well-documented history of exhibiting potent antioxidant properties. Moreover, numerous studies have reported its efficacy in attenuating inflammatory responses [13]. These findings indicate that thyme may hold promise as an anti-inflammatory agent, particularly due to its high content of hesperidin.…”
Section: Phytochemical Studymentioning
confidence: 92%
“…A Vernier caliper (Mitutoyo, Japan) was used to measure the ankle swelling (mm) in the paw due to the FCA injection every 7 days . Experimental animals were divided into five groups with six rats in each group as follows: Normal control (N) group: These animals received 0.9% NaCl solution as an oral vehicle and routine diet and water. Arthritic control (AC) group: The rats treated with the FCA model received oral vehicle 0.9% NaCl solution and normal feed and water for 28 days. Arthritic treated (H) group: RA rats received the quercetin suspension at a dosage of 15 mg/kg , and normal NaCl solution and a routine diet. Arthritic treated (ST) group: All the rats in this group after induction of rheumatoid arthritis received the quercetin-loaded nanoparticles in suspension form at a dose of 15 mg/kg. Dexamethasone-treated (H) group: The rheumatoid arthritis rats received the normal diet of water and dexamethasone suspension (at a dose of 0.3 mg per kilogram of rat weight). …”
Section: Methodsmentioning
confidence: 99%
“…Arthritic treated (H) group: RA rats received the quercetin suspension at a dosage of 15 mg/kg , and normal NaCl solution and a routine diet.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations